1988
DOI: 10.2118/15442-pa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Capillary Pressure on Coalescence and Phase Mobilities in Foams Flowing Through Porous Media

Abstract: Summary. The stability of foam lamellae is limited by capillary pressure. Consequently, as the fractional flow of gas in a foam is raised at a fixed gas velocity, the capillary pressure in a porous medium at first increases and then approaches a characteristic value, here called the "limiting capillary pressure." If the gas fractional flow is increased after the limiting capillary pressure has been attained, coalescence coarsens foam texture, the liquid saturation remains constant, and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
344
4
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 458 publications
(385 citation statements)
references
References 13 publications
34
344
4
1
Order By: Relevance
“…This sort of cycling was observed by Khatib et al (1988) in their original study of the limiting capillary pressure. In these cases, the average pressure drop in the cycle is used in constructing Figs.…”
Section: Subtask 22: Co 2 Foam Experimentsmentioning
confidence: 62%
“…This sort of cycling was observed by Khatib et al (1988) in their original study of the limiting capillary pressure. In these cases, the average pressure drop in the cycle is used in constructing Figs.…”
Section: Subtask 22: Co 2 Foam Experimentsmentioning
confidence: 62%
“…The methods of calculating two-dimensional displacements to 3-D systems by tracing streamlines from injectors to producers developed by Thiele et al 12 have been successfully extended. The examples given highlight the advantage of the streamline technique over conventional finite-difference results.…”
Section: Discussionmentioning
confidence: 99%
“…At the high-quality regime, the pressure gradient is almost independent of the gas flow rate. Previous studies found that the two regimes are dominated by different mechanisms: the high-quality regime by bubble coalescence near the critical capillary pressure and the low-quality regime by bubble trapping and mobilization (Khatib et al 1988;Rossen and Wang 1999; 4.3 Alvarez et al 2001). The bubble size in the low-quality regime is generally kept roughly the same as the pore size, and thus foam texture (n f ) is almost fixed at its maximum (n f max ).…”
Section: Regimes Of Foam Flowmentioning
confidence: 97%